(untitled) (Pulse, 2017)
Background: A meningioma is a tumor that arises from the meninges- the membranes that surround the brain and spinal cord. Objective: This is a retrospective analysis of the recorded data of patients managed for intracranial meningiomas between January 2007 and June 2015 at Apollo Hospital, Dhaka. Methodology: Demographic data was analyzed for all but only patients who had surgery and histological diagnosis were analyzed for outcome. Results: This study shows that meningiomas had female preponderance. Majority cases were above 50 years of age. Convexity is the most common anatomical location of meningioma. Most common symptoms were headache (70%) followed by seizure in 34.3% of patients. 90% of the cases were benign. Malignant meningioma was 1.4% and recurrence was found in 1.4% of cases. Six patients with histological grades I, II and III meningi- omas were sent for stereotactic radiotherapy after incomplete tumor resection or for residual tumour. Total removal was done in 80% cases and the mortality was 1.4%, in patient who had poor GCS score on admission. Pulse Vol.9 January-December 2016 p.22-26